18 A UK palliative trainee research collaborative: new knowledge through networking. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Chamberlain, Charlotte; Schofield, Guy; Hancock, Sophie; Etkind, Simon; Robbins, Sara; Werrett, Felicity; Coop, Hazel; Watson, Rebecca; Koffman, Jonathan; Noble, Simon
Abstract : Background: The first UK trainee research collaborative was established in 2006 and the majority (39/45) are surgical or anaesthetic based. Trainee collaboratives harness the resource of doctors in training for multicentre audit and research. Collaboratives have spearheaded quality improvement projects, audit, systematic reviews and recruitment for national and international studies. Collaboratives have also demonstrated increased trainee research exposure over time, with trainee involvement in design, ethics, data analysis, and manuscript preparation. Palliative medicine research is relatively underfunded, and trainee research exposure varies significantly across rotations. Our small specialty has much to gain from the development of the first UK wide palliative trainee research collaborative. Methods: The UK Palliative Care Trainee Research Collaborative (UKPRC) was established in 2017. Modelled on other successful trainee collaboratives, we employed the following steps: Writing and adopting a constitution that enshrines shared authorship as a central tenant; Identifying a core group of interested trainees; Nominating a clinical and research lead; Defining a brand; logo, website, email address, newsletter and twitter profile; Choosing a project; Recognising crucial stakeholders to disseminate information and garner support. Results: Launched publicly in August 2018, the UKPRC already has members from 12/14 of the UK deaneries. The first national audit project is underway aiming to recruit 40 sites across all sectors in the UK. The UKPRC has a website, 186 followers on twitter and has been discussed by the APM and the National Clinical Research network leads in palliative and supportive care in the UK. Conclusions: The UKPRC has the potential to conduct audit and research across hospice and hospital sectors UK wide, which will inform evidence-based practice and ultimately aims to improve patient care. Collaboratives may strengthen the research culture within palliative medicine, embedding research activity and evidence-based practice from the first year of training.